THE COLLECTIVE FUTURE OF HIGHER EDUCATION: UNVEILING THE ROLE OF VALUES IN ONLINE LEARNING - Adams, Katherine Elizabeth (Top Journal of Public Policy and Administration (TJPPA), 2023)
This study critically examines the evolving landscape of online learning and its potential implications for higher education in the context of the COVID-19 pandemic. The extensive literature on the future of online education and its intersection with technology is explored. Borden's assertion of a transformative period in education within the digital age, compounded by the challenges posed by the ongoing pandemic, is investigated. Borden calls for the creation of a solid framework for online learning but does not provide specific recommendations or policy guidelines. Govidnarajan and Srivastava's argument that the pandemic serves as a catalyst for global experimentation in higher education, necessitating dramatic reform due to rising costs, is analyzed. Their claim that this experimentation will enrich political discourse and lead to free college education is evaluated for its practicality and feasibility, considering the deeply entrenched cultural norms within educational institutions. This study aims to shed light on the potential future of online learning in higher education, with a focus on identifying practical approaches and policy recommendations. It critically assesses the challenges and opportunities posed by the digital age and the pandemic, highlighting the need for a well-defined framework to guide online education initiatives.